A Case of Aortic Regurgitation and Hypotension - Chan, Laura Lihua; Chin, Chee Tang (International Journal of Angiology, 2013)
Takayasu arteritis is a chronic inflammatory large vessel vasculitis affecting the aorta and its main branches. It can present in various forms, and thereby may lead to a delay in diagnosis. We present a patient with Takayasu arteritis, diagnosed at our center when she presented with severe aortic regurgitation. We also review the current knowledge base with respect to Takayasu arteritis.
Keywords: Takayasu arteritis; aortic regurgitation; vasculitis; hypotension